Spectral Characterization and Detection of Bud Rot on Oil Palm in Puntarenas, Costa Rica - Martínez-Barbáchano, Rubén (2018)
During the last decades, precision agriculture has observed significant technical progress that has permitted better management of farming, optimizing resources and applied inputs. Within the scope of geomatics, land optical sensors have allowed to expand and increase knowledge on the spectral behavior of the crops under study, providing increased benefits in the application of treatments and pest or disease prevention. The objective of this work was to characterize the African oil palm (Elaeis guineensis Jacq.), by means of field radiometry-spectrum, in healthy plants, as well as in plants affected by bud rot. The study was conducted between March and May 2016 in African oil palm farms in Parrita, Puntarenas, Costa Rica. A hyperspectral land sensor, with a 325-1075 nm wavelength range (visible and near-infrared spectrum), was used. In general, plants in healthy phytosanitary condition, which also had a treatment of “fertilization+irrigation”, presented the highest reflectivity curves: around 0.7%. The bud rot influence in the reflectance curve of the plants had, in most cases, a greater weight than the type of treatment to which they are subjected. It thus confirms the possibility of detecting the bud rot pathology through reflectance spectroscopy in conditions of field work, the main goal of this research. Keywords: Spectroscopy, near infrared, reflectance, land optical sensors.